Артеріальна гіпертензія у хворих на акромегалію: акцент на кардіоваскулярний ризик - Микитюк, М. Р. (Clinical Endocrinology and Endocrine Surgery, 2013)
There are several complications of the cardiovascular system caused by acromegaly, especially arterial hypertension (AH). To evaluate AH characteristics in patients with cured-controlled (n=11) acromegaly and with the active disease (n=111). AH was detected in 60,7% of patients. Subjects with active disease showed a positive correlation between IGF-1 and systolic (SBP) and diastolic (DBP) blood pressure (BP) levels (r=0,26, p=0,013) and (r=0,28, p=0,007, respectively), and a positive correlation between insulin like growth factor 1 (IGF-1) and urinary albumin excretion rates (r=0,27, p=0,04). In patients with active disease, IGF-1 was a predictor of SBP. For individuals with cured-controlled disease, waist circumference and age were the predictors associated with SBP and DBP. Our findings suggest that BP levels in patients with active acromegaly are very similar, and depend on excess IGF-1. However, once the disease be comes controlled and IGF-1 levels decrease, their BP levels will depend on the other cardiovascular risk factors.